Oxidation and nitridation of vitreous carbon at high temperatures. (15th October 2020) - Murray, Vanessa J.; Recio, Pedro; Caracciolo, Adriana; Miossec, Chloe; Balucani, Nadia; Casavecchia, Piergiorgio; Minton, Timothy K.
Abstract: Molecular beam-surface scattering experiments were used to obtain fundamental data on gas-surface interactions that are central to the ablation of carbon during hypersonic flight through air. Continuous beams containing O or N atoms with incident velocities of ∼2000 m s −1 were directed at a vitreous carbon surface at temperatures in the range, 800–1873 K, and the products that desorbed from the surface were detected with a rotatable mass spectrometer detector as a function of their velocity and scattering angle. All products exhibited the dynamical characteristics of thermal desorption. The efficiencies of the gas-surface interactions, both reactive and non-reactive, were quantified as a function of surface temperature. In addition to reacting with carbon to produce CO2 (minor product) and CO (major product), oxygen atoms may recombine on the surface to produce O2 with an efficiency that is somewhat lower than that to produce CO. Nitrogen atoms may recombine on the surface to produce N2 or react to produce CN. The recombination efficiency of N atoms is generally more than an order of magnitude higher than the reaction efficiency to produce CN. The quantitative reaction efficiencies reported here are useful for the development of air-carbon models for hypersonic ablation. Graphical abstract: Image 1